Urgensi Pengembangan Konseling Spiritual Bagi Pecandu Narkoba Untuk Mereduksi Thanatophobia - M. Fahli Zatrahadi; Neviyarni Suhaili; Ifdil Ifdil; Marjohan Marjohan; Afdal Afdal (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
We can reduce the psychological phenomenon of thanatophobia in clients by carrying out spiritual counseling and religious beliefs. This study discusses the urgency of spiritual counseling for drug addicts who experience the psychological phenomenon of thanatophobia. The research method is qualitative with the following stages: determining questions, collecting informant data, getting data, and reporting. The informants comprised two counselors, three residents of the Tampan Mental Hospital, Drug Installation, and three experts. The results showed that spiritual counseling could reduce anxiety about death in clients, but in terms of its implementation it was still not optimal because implementing spiritual counseling at the Tampan Mental Hospital with Drug Installation was carried out by the help of ustad/religious leaders in collaboration with counselors.